Amino acids substitutions in the PB2 protein of H7N9 influenza A viruses are important for virulence in mammalian hosts - Yamayoshi, Seiya; Fukuyama, Satoshi; Yamada, Shinya; Zhao, Dongming; Murakami, Shin; Uraki, Ryuta; Watanabe, Tokiko; Tomita, Yuriko; Neumann, Gabriele; Kawaoka, Yoshihiro (Scientific reports, 2015)
We tested the biological significance of two amino acid mutations in the PB2 protein (glutamic acid to lysine at position 627 and aspartic acid to asparagine at position 701) of A(H7N9) viruses for mammalian adaptation. Mutants were assessed for their viral polymerase activities, growth kinetics in mammalian and avian cells and pathogenicity in mice. We found that lysine at position 627 and asparagine at position 701 in PB2 are essential for mammalian adaptation of A(H7N9) viruses.